Controllable Crystallization of Two‐Dimensional Bi Nanocrystals with Morphology‐Boosted CO2 Electroreduction in Wide pH Environments - Chen, Li‐Wei; Hao, Yu‐Chen; Li, Jiani; Hu, Linyu; Zuo, Xintao; Dai, Chunlong; Yu, Zi‐Long; Huang, Hui‐Zi; Tian, Wenjing; Liu, Di; Chang, Xiaoxue; Li, Pengfei; et al. (Small (Weinheim an der Bergstrasse, Germany), 2023)
Two‐dimensional low‐melting‐point (LMP) metal nanocrystals are attracting increasing attention with broad and irreplaceable applications due to their unique surface and topological structures. However, the chemical synthesis, especially the fine control over the nucleation (reduction) and growth (crystallization), of such LMP metal nanocrystals remains elusive as limited by the challenges of low standard redox potential, low melting point, poor crystalline symmetry, etc. Here, a controllable reduction‐melting‐crystallization (RMC) protocol to synthesize free‐standing and surfactant‐free bismuth nanocrystals with tunable dimensions, morphologies, and surface structures is presented. Especially, ultrathin bismuth nanosheets with flat or jagged surfaces/edges can be prepared with high selectivity. The jagged bismuth nanosheets, with abundant surface steps and defects, exhibit boosted electrocatalytic CO2 reduction performances in acidic, neutral, and alkaline aqueous solutions, achieving the maximum selectivity of near unity at the current density of 210 mA cm–2 for formate evolution under ambient conditions. This work creates the RMC pathway for the synthesis of free‐standing two‐dimensional LMP metal nanomaterials and may find broader applicability in more interdisciplinary applications. Ultrathin, free‐standing, and surfactant‐free bismuth nanosheets were synthesized by the controllable reduction‐melting‐crystallization method. Increasing the high‐index facets of bismuth nanosheets can modify their surface electronic structures to strengthen the adsorption of CO2, lower the reaction energy barriers, and promote CO2 reduction reaction selectivity and activity for formate in wide pH environments, realizing high‐energy‐efficiency CO2‐to‐HCOOH conversion in a flow cell system.